Advanced Analysis of Coumarin-Based Al/PSi Photodetectors with Fytronix Solar Simulator Technologies - Yalcin, Mesut; Dere, Aysegul; Yakuphanoğlu, Fahrettin (Springer, 2026)
Coumarin-based organic layers have attracted considerable attention in optoelectronic device applications due to their favorable optical and electronic properties. However, the incorporation of bathocuproine (BCP) into a coumarin/p-Si architecture and its systematic evaluation in terms of responsivity, detectivity, photocapacitance, and interface state density have not been systematically reported. In this study, coumarin-BCP composite layers containing 10 wt% and 20 wt% BCP were prepared, and Al/p-Si/coumarin:BCP/Al devices were fabricated. The electrical and optoelectronic properties were investigated under visible-light illumination (20-100 mW/cm2). The device containing 20% BCP exhibited enhanced performance, achieving a responsivity of 54.62 mA/W and a specific detectivity of 1.69 & times; 1012 Jones at 100 mW/cm2, compared to 18.64 mA/W and 5.77 & times; 1011 Jones for the 10% BCP device. The improved photoresponse is attributed to enhanced charge transport and interface-related effects induced by increased BCP concentration. These results demonstrate that coumarin-BCP composite-based Al/p-Si devices are promising candidates for visible-light photodetector and photosensor applications.
Keywords: Performance; Devices; Layer